From verbal prefixes to direction/result markers in Romance - Cordin, Patrizia (Linguistica (Ljubljana), 2011)
In this paper I analyze verb-locative constructions in Romance. Even though not allowed in standard Romance languages, which have maintained and codified the classical Latin prefix system, these constructions are widely attested in non standard varieties, that are scarcely (or not at all) regularized. In this paper I deal in particular with a northern Italian variety, Trentino, where locatives, combining with some classes of verbs (unaccusative verbs and transitive activity verbs) can express not only concrete direction and metaphorical direction, but also aspect (the result of an activity or the progress of a process); in other words, they can express an abstract, more grammaticalized feature of direction. In fact, Trentino verb-locative constructions can express a specific phase of the development of an event, often the result (end-point) of an activity, or the start-point, or the progress, or the intensity of the activity itself. I argue that in Trentino (and in other similar dialectal varieties) locatives can function as grammatical markers both for arguments (in combination with motion verbs) and for aspect (in combination with verbs involving the feature of an abstract path). In a more general context, I note that locatives in combination of verbs function as goal/result markers in those varieties that tend to spell out markers of functional elements, frequently generating a repetition (doubling) of the same feature. Finally, I compare Romance and Germanic constructions, noting that diachronic, grammatical and typological differences (with particular reference to Talmy's distinction between verb-framed languages and satellite languages) confirm the independence of Romance verb-locative constructions.
Keywords: glagol; langues romanes; marqueurs de direction; označevalci smeri; parler de Trentino; prosti morfemi; romanski jeziki; trentinski govor; verb; verbe